US monetary policy and the euro area - Max Hanisch (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This study investigates the international spillover effects of contractionary US monetary policy and its transmission channels on members of the euro area (EA) before and after the implementation of the euro. I find the multilateral spillover effects on individual EA economies' real activity and inflation to be asymmetric, i.e. the responses are mainly expansionary but not exclusively so. While the effects are diverse and rather large before 1999, responses become more homogeneous and smaller in size after the implementation of the euro. However, country-specific asymmetries remain. Trade and interest rates but also credit, stock and housing markets are identified as important transmission channels.
Is replaced by the following version: http://hdl.handle.net/10419/201416
Keywords: C32; E52; E58; 330; Structural dynamic factor model; Sign restrictions; Monetary policy; US; Euro Area; Spillover effects